Acute Non-Erosive Gastritis Associated with Irregular Dietary Habits and Psychological Stress in a Young Adult - Rinto Hardiarto; Athifah Dewi Ghinaa Yusriyyah; Audry Rizki Hasanah; Aufa Nabila Rahmalya; Azzelia Zaskia Alifah; Belinda Dewi (Biomedical Research and Theory Letters, 2025)
Acute gastritis is a common gastrointestinal disorder characterized by sudden inflammation of the gastric mucosa, frequently associated with dietary irritation, psychological stress, and dysregulation of gastric acid secretion. Although generally considered a benign and self-limiting condition, acute gastritis may significantly impair daily functioning, particularly among young adults with irregular lifestyles. This article describes the clinical course and holistic management of acute non-erosive gastritis in a young adult, emphasizing the contribution of modifiable behavioral and psychosocial factors. A 24-year-old woman presented to a primary healthcare facility with a four-day history of epigastric burning and pressing pain, aggravated by delayed meals and the consumption of spicy and acidic foods. The patient reported irregular eating patterns and considerable academic- and work-related psychological stress. There was no history of NSAID use, alcohol consumption, smoking, or previous gastrointestinal disease. Clinical assessment was conducted through structured history taking, comprehensive physical examination, and anthropometric measurement. No laboratory or endoscopic investigations were initially performed due to the absence of alarm features. The diagnosis of acute non-erosive gastritis was established based on clinical criteria. Management consisted of an integrated approach combining pharmacological and non-pharmacological interventions. Pharmacological therapy included omeprazole 20 mg once daily to suppress gastric acid secretion and antacids administered as needed for symptomatic relief. Non-pharmacological management focused on patient and family education regarding gastric-friendly dietary patterns, regular meal timing, avoidance of trigger foods and beverages, and stress management strategies. Follow-up evaluation was planned to monitor symptom resolution and determine the need for further diagnostic investigations, including Helicobacter pylori testing or endoscopy, if symptoms persisted or worsened. Following the initiation of combined therapy and lifestyle modification, the patient demonstrated clinical improvement with reduced frequency and intensity of epigastric pain. This case underscores the importance of addressing lifestyle and psychosocial contributors in addition to pharmacological treatment in acute gastritis. The novelty of this report lies in its explicit integration of holistic clinical assessment including functional, psychological, and family-based factors within the management of acute gastritis in a young adult, highlighting a practical, patient-centered model that may reduce symptom recurrence and improve long-term outcomes in primary care settings.